EVALUASI APLIKASI ARAHKAN (Ayo Realisasikan Administrasi Harmonis Perikanan) DI UPT PELAYANAN USAHA PERIKANAN KECAMATAN KUNDUR - Asrul Muhayat; Novi Winarti; Ardi Putra (PT. Jurnal Center Indonesia Publisher, 2024)
The Karimun Regency Government is improving fisheries business services through the Fisheries Service creating an online-based service innovation in the form of the ARAHKAN (Let's Realize Harmonious Fisheries) Application in realizing fisheries administration services that are fast, cheap, efficient and transparent. This research discusses matters related to the implementation of fisheries business services using technology and obstacles in application services. The aim of this research is to find out how application-based fisheries business services are at the Fisheries Business Services UPT, Kundur District, Karimun Regency. The method used in this research is a qualitative descriptive method with informants consisting of elements from the Fisheries Service, UPT and the community and using data collection techniques and tools in the form of observation, interviews and documentation. The overall research results of this application have been said to meet expectations based on the following 4 indicators: a) input: human resources, finances, adequate facilities and infrastructure. b). Process: easy procedure, more time and cost efficient. c). Output: service levels increase, such as Kube, fuel recommendations, benefits received by fisheries business actors increase. d). Outcome: fisheries business services are more effective and efficient. However, in terms of the implementation process it cannot be said to have met expectations because there are still obstacles or obstacles such as network problems, the community is not yet technologically independent. Keywords : Services, Policy Evaluation, Electronic Services